Exposure to traffic related air pollutants: self reported traffic intensity versus GIS modelled exposure. Issue 8 (26th July 2005) - Heinrich, J; Gehring, U; Cyrys, J; Brauer, M; Hoek, G; Fischer, P; Bellander, T; Brunekreef, B
Abstract : Background: In epidemiological studies of the potential health effects of traffic related air pollution, self reported traffic intensity is a commonly used, but rarely validated, exposure variable. Methods: As part of a study on the impact of Traffic Related Air Pollution on Childhood Asthma (TRAPCA), data from 2633 and 673 infants from the Dutch and the German-Munich cohorts, respectively, were available. Parents subjectively assessed traffic intensity at the home address. Objective exposures were estimated by a combination of spatial air pollution measurements and geographic information system (GIS) based modelling using an identical method for both cohorts. Results: The agreement rates between self reported and GIS modelled exposure—accumulated over the three strata of self assessed traffic intensity—were 55–58% for PM2.5, filter absorbance (PM2.5 abs), and nitrogen dioxide in Munich and 39–40% in the Netherlands. Of the self reported low traffic exposed group, 71–73% in Munich and 45–47% in the Netherlands had low modelled exposure to these three air pollutants. Of the self assessed high exposed subgroups in Munich (15% of the total population) and the Netherlands (22% of the total population), only 22–33% and 30–32% respectively had high modelled exposure to the three air pollutants. The subjective assessments tend to overestimate the modelled estimates for PM2.5 and NO2 in both study areas. When analysis was restricted to the portion of the Dutch cohort living in non-urban areas, the agreement rates were even lower. Conclusions: Self reported and modelled assessment of exposure to air pollutants are only weakly associated.